Triangular Grids: A Review of Resonator and Waveguide Analysis with Classical FIT and Some Reflections on Yee-like FIT- and FEM-Schemes - RIENEN, URSULA VAN (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The focus of this paper is on the solution of Maxwell’s equations on triangular orthogonal grids for timeharmonic elds in cylindrically symmetric resonators and general time dependant elds in length-homogeneous waveguides, respectively. The method is based on the Finite Integration Technique (FIT) [1], [2]. The 2D simulation on a structured triangular grid combines the advantages of FIT, as e.g. the consistency of the method or the numerical advantage of banded system matrices, with the geometrical exibility of noncoordinate grids. FIT on triangular grids was rst introduced in [3], [4]1. This paper presents a review describing the underlying theory in FIT operator notation rst introduced in [2] and puts this classical approach for FIT on triangular grids in relation to actual research in the eld.